Odpowiedzi

2010-01-11T19:42:04+01:00
13e-5(f-3e)= 13e -5f+15e=28e-5f

4(-2r+s)-10,5r= -8r+ 4s - 10,5r =-18,5r+4s

-3(3x-2y)+2(x-2y)= -9x+6y +2x-4y =-7x+2y

-5(2z-3y)-4(4z-2y)= -10z+15y -16z+8y = -26z+23y

2(2p-3q+7)-3(p-2q+4)= 4p -6q+14-3p+6q-12 = p+2

2(3x²-2y+5y²)-3(4y+5y²)+2x-3x= 6x²-4y+10y²-12y-15y²-x=6x²-5y²-16y


powinno byc dobrze ;D





Najlepsza Odpowiedź!
2010-01-11T19:47:02+01:00
3e-5(f-3e)=3e-5f+15e=18e-5f
4(-2r+s)-10,5r= -8r+4s-10,5r=-18,5r+4s
-3(3x-2y)+2(x-2y)=-9x+6y+2x-4y= -7x+2y
-5(2z-3y)-4(4z-2y)= -10z+15y-16z+8y= -26z+23y
2(2p-3q+7)-3(p-2q+4)=4p-6q+14-3p+6q-12=p+2
2(3x²-2y+5y²)-3(4y+5y²)+2x-3x=6x²-4y+10y²- 12y+15y²+ 2x-3x=
6x²+25y²-x-16